2015
DOI: 10.1016/j.ajog.2015.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Health care justice and its implications for current policy of a mandatory waiting period for elective tubal sterilization

Abstract: Tubal sterilization during the immediate postpartum period is 1 of the most common forms of contraception in the United States. This time of the procedure has the advantage of 1-time hospitalization, which results in ease and convenience for the woman. The US Collaborative Review of Sterilization Study indicates the high efficacy and effectiveness of postpartum tubal sterilization. Oral and written informed consent is the ethical and legal standard for the performance of elective tubal sterilization for perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Support of such regulations may imply a belief that these women are unable to make decisions regarding sterilization in a fully informed manner. 21,22 Our study found that 43.5% of the women who did not get sterilization had changed their minds and declined sterilization in the immediate postpartum period, consistent with other studies. 5,23 This group represented more than double the total number of women who did not receive sterilization because of all other external barriers (18.6%), including lack of available operating room, often because of the elective nature of tubal ligation, and physician decision against the procedure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Support of such regulations may imply a belief that these women are unable to make decisions regarding sterilization in a fully informed manner. 21,22 Our study found that 43.5% of the women who did not get sterilization had changed their minds and declined sterilization in the immediate postpartum period, consistent with other studies. 5,23 This group represented more than double the total number of women who did not receive sterilization because of all other external barriers (18.6%), including lack of available operating room, often because of the elective nature of tubal ligation, and physician decision against the procedure.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have spoken to the implications of the Medicaid consent regulations applying solely to a low‐income population of women. Support of such regulations may imply a belief that these women are unable to make decisions regarding sterilization in a fully informed manner . Our study found that 43.5% of the women who did not get sterilization had changed their minds and declined sterilization in the immediate postpartum period, consistent with other studies .…”
Section: Discussionsupporting
confidence: 89%
“…Still, those women who may be the most desperate for sterilization, women with significant social issues and high parity who fall between the cracks in our system, already have trouble accessing prenatal care and thus are most at risk for not meeting mandated criteria for sterilization consent. Multiple analyses and commentaries have underscored the need for re-evaluating the requirements for this mandated consent process in order to continue to ensure informed consent while respecting patient autonomy and removing barriers to desired procedures, which disproportionally affect socially disadvantaged patients [1013]. …”
Section: 0 Discussionmentioning
confidence: 99%
“…The task of perinatal ethics is to specify what is due to the stakeholders e pregnant, fetal, and neonatal patients e on the basis of beneficence-based and autonomy-based obligations to the pregnant patients, beneficencebased obligations to the fetal patient, and beneficence-based obligations to the neonatal patient. This is known as healthcare justice [15]. We identify challenges to healthcare justice in the allocation of healthcare resources to these patients and show how the professional responsibility model of perinatal ethics should guide perinatologists in responding to these challenges.…”
Section: Implications For Global Perinatologymentioning
confidence: 96%